2018
DOI: 10.1007/s00535-018-1473-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-world virological efficacy and safety of elbasvir and grazoprevir in patients with chronic hepatitis C virus genotype 1 infection in Japan

Abstract: The EBR/GZR regimen yielded high virological efficacy with acceptable safety. Patients with a history of failure to IFN-free DAA therapy or with double RASs in HCV-NS5A remained difficult to treat with this regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
3
25
5
Order By: Relevance
“…SVR12 rates remained high across other important participant subgroups, including those with compensated cirrhosis, with a baseline viral load > 2 000 000 IU/mL, and aged ≥ 65 years, but SVR12 was lower in participants with GT1a infection. These data support the findings from the EBR/GZR phase 3 clinical development program in both Asian and white individuals and are also consistent with several recent studies reporting SVR rates of 94–98% in Japanese individuals with HCV GT1 infection following treatment with EBR/GZR …”
Section: Discussionsupporting
confidence: 91%
“…SVR12 rates remained high across other important participant subgroups, including those with compensated cirrhosis, with a baseline viral load > 2 000 000 IU/mL, and aged ≥ 65 years, but SVR12 was lower in participants with GT1a infection. These data support the findings from the EBR/GZR phase 3 clinical development program in both Asian and white individuals and are also consistent with several recent studies reporting SVR rates of 94–98% in Japanese individuals with HCV GT1 infection following treatment with EBR/GZR …”
Section: Discussionsupporting
confidence: 91%
“…Therapy with EBR/GZR achieved a high SVR rate and high tolerability in the present study based on actual clinical practice, similar to a Japanese phase III trial. As in the report by Toyoda et al ., the SVR rate was consistent regardless of various factors such as age, sex, eGFR, and HCC treatment history. Patients with chronic renal disorders, including those on dialysis, also showed a comparable SVR rate.…”
Section: Discussionsupporting
confidence: 83%
“…Only 2.9% (10/353) of patients in the current study showed treatment failure, and these patients had a history of DAA therapy or a double mutation at NS5A‐L31/‐Y93. Investigations have found that few patients who fail to respond to DAA treatment respond to EBR/GZR therapy . However, SVR was achieved in six of seven patients who had a history of DAA therapy but no double mutation at NS5A‐L31/‐Y93 in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…Although daclatasvir/asunaprevir and ombitasvir/paritaprevir/ritonavir are less effective for patients with NS5A RASs, a randomized phase 2/3 study conducted in Japan suggested that EBR/GZR is highly effective for these patients. However, a multicenter, real‐world study reported that reduced efficacy of EBR/GZR in patients with both the preexisting NS5A L31 and Y93 RASs and in those with a history of treatment failure with IFN‐free DAA …”
Section: Discussionmentioning
confidence: 99%